Travelers' Use of ICT under Conditions of Risk and Constraints: An Empirical Study Based on Stated and Induced Preferences. (October 2014) - Lu, Ruihua; Chorus, Caspar; van Wee, Bert
A discrete choice model is presented of travelers' decisions whether or not to use different forms of ICT (travel information and teleworking) in the context of risky travel times and arrival time constraints. The model is estimated on data from two travel simulator experiments. One experiment featured a reward which was related to participants' choices (implying a so-called induced-preference approach). The other experiment featured a fixed participation fee (a stated-preference approach). Results suggest that the developed model succeeds in capturing subtle behaviors related to the use of ICT; evidence for the usefulness of the induced-preference approach is mixed, at best.